Two new species of the gobiid fish Trimma from the coral reefs of THE western Pacific Ocean (Pisces; Perciformes; Gobioidei) - Winterbottom, Richard (Zootaxa, 2006)
Two new species of the gobiid fish genus Trimma are described. Both possess scales in the predorsal midline, have interorbital and postorbital trenches, and lack scales on the opercle. Trimma anthrenum is characterized by an unbranched fifth pelvic fin ray and an almost monochromatic color pattern. When alive, it has a yellow body, and the iris has a pair of blue and black triangles with their bases against the anterior and posterior margins of the pupil (giving the pupil a slit-like appearance), the posterior triangle continues anteroventrally around the pupil margin. Preserved specimens have a very finely outlined diamond pattern across the dorsal half of the body, which otherwise exhibits very few melanophores or chromatophores, a concentration of pigment on the top of the pectoral base, with little pigment on the base itself, a short line of melanophores just above the opercle, and strong basal black bands in the dorsal and anal fins. The species is currently known from Fiji and Tonga. Trimma preclarum is characterized by an elongate second and third dorsal spines and a fifth pelvic ray that may or may not be branched (depending on locality). When alive, Trimma preclarum has three yellow stripes extending along the body, and a red to purple-red iris with four large yellow spots. Preserved specimens have a finely outlined diamond pattern across the dorsal half of the body, and a diffuse, attenuating band of pale brown chromatophores over the abdomen which fades out above the anal fin. The species has been found at Fiji, Palau, Solomon Islands and Papua New Guinea, with underwater photographs from Saipan.